Should government of the people's republic of Bangladesh directly operate Micro Credit? - Hamidi, MD. Saiful Alam (KDI School, 2000)
Economic development and poverty alleviation are important goals of every developing nation of the world. Since the 1950s and 1960s several development strategies, such as ‘growth with industrialization, ‘growth with sectoral balance’ and ‘growth with equity’ have been implemented in attempts to achieve economic development in these counties. Of late, liberalization and export orientation have become the catch cries of development policy. These approaches have had mixed results; in all cases, capital, labor and technology have been regarded as the main inputs to development. With some variations, most developing countries registered upward growth during the last three decades, and certain Asian countries have achieved the most impressive results of all. But despite this record, not all Asian countries achieved similar growth, nor, as is evident, were the successes in economic growth matched by similar successes in poverty alleviation. In some countries, economic development was accompanied by gross inequality. Examination of the causes of incongruities between planning and development and between development and poverty alleviation has revealed that quite often, ‘governance’ is a more important factor than capital, labor and technology in inducing growth and ensuring equity in a society. It has been argued that good governance ensures good vision and pragmatic direction for the economy, creates enabling environment for investment opportunities, guarantees rational allocation of resources and their proper use, and maintains political commitment to and a sense of urgency about economic development and poverty alleviation. Governance has been defined as the manner in which power is exercised in the management of a country’s economic and social resources for development (World Bank, 1992)’. The research paper presents a framework describing the relationship between role of government, poverty alleviation as well as rural development through micro credit operation. The micro credit programs operated by GO and NGOs in Bangladesh are the main issue covered in this paper and the paper concluded that more than anything else, urgent measures should be taken to determine the role of bureaucracy as well as government of Bangladesh in operation of micro credit for eradicating poverty
Thesis(Master) --KDI School:Master of Growth and Development Studies,2000